Assessment of Risk Behaviors and Toxic Heavy Metals Exposure of Car Dye Workers in Repairing Services in Erbil City, Kurdistan Region, Iraq - Hawraz Sami Khalid; Shokhan Sherzad Hamadamin; Hanan Salm Salih (Zanco Journal of Pure and Applied Sciences, 2020)
The main objective of this study was to determine blood cadmium (BCd) and blood lead (BPb) contents for 16 car dye workers in repairing service and compared to those of 16 controls (non-occupational exposed subjects) in Erbil City, Kurdistan Region, Iraq. Strong wet acid digestion method was applied to digest whole blood samples using a mixture H2O2 (50% v/v) and HNO3 (65% v/v) with a volume ration (1:2). Inductively coupled plasma - optical emission spectrometer (ICP-OES) was used to determine these toxic metals in collected whole blood samples. The recorded mean of BCd and BPb contents in subjected painters were higher levels compared to the control group. The mean ± standard deviation (SD) contents of BCd and BPb of painters were 2.93±2.35 μg/L and 32.19±16.95 μg/L, respectively. The mean ± SD contents of BCd and BPb of controls were 0.870±0.34 μg/L and 22.46±12.55 μg/L, respectively. A set of formal investigation questionnaire was performed to know participants history profile, smoking status, clinical profile, the risk behaviors at the workplace, and occurrence symptoms. The results showed that the percentages of occurrence of most investigated symptoms (especially respiratory and musculoskeletal) system on the experimental painters were significantly (p-value = 0.016) higher than those symptoms of the control group. The collected data on risk behaviors confirmed that personal protection equipment (PPE) had not been concerned by most of the experimental painters. Duration of work (years), and the use of PPE (wearing a respirator) were noticeably associated with BCd and BPb levels of painters.